Enhancing Elderly Protection in Modern Family Structures: Intergenerational Perspectives, Regulatory Innovations, and the Direction of Socio-Cultural Services in Indonesia - Khoiruddin, Muhammad; Waksito, Sarwo; Wijaya, Kurnia (Journal of Social Science Studies, 2024)
This study aims to analyses legal protection for the elderly within families based on an intergenerational perspective and current social dynamics in Indonesia. This qualitative literature study utilizes a thematic synthesis method, analyzing laws, public policies, and scientific literature to map changes in family functions and formulate the characteristics of legal protection for the elderly. The findings show that although regulations such as Law No. 13 of 1998 have regulated the rights of the elderly, the imbalance of roles between generations, weak law enforcement, and the fragmentation of values in modern families create new vulnerabilities for the elderly. Regulatory reform, the development of community-based social services, and technology-based innovations are considered important to improve the effectiveness of elderly protection. The contribution of this research lies in emphasizing the importance of synergy between legal, religious, and cultural norms and strengthening intergenerational literacy so that the rights, respect, and welfare of the elderly can be achieved sustainably amid the transformation of modern society. The practical implications of this study are directed at policy formulation, strengthening family capacity, and developing participatory social service innovations for the elderly.